Academic inbreeding and publication activities of Russian faculty. Issue 1 (2nd January 2018) - Alipova, Olga; Lovakov, Andrey
Abstract : The literature on the consequences of academic inbreeding shows ambiguous results: some papers show that inbreeding positively influences research productivity measured by the quantity and quality of publications, while others demonstrate the opposite effect. There are contradictory results both in the studies of different countries and within countries. This variety of results makes it impossible to transfer the findings from one academic system to another, and in Russia this problem has been under-explored. This paper focuses on the relationship between inbreeding and publication activity among Russian faculty. The research was conducted using data from the 'Monitoring of Educational Markets and Organizations' survey. The results show that there is no significant effect of academic inbreeding on publication productivity: no substantial and robust differences in publication activity between inbreds and non-inbreds have been found. The paper finishes with a discussion of possible explanations inherent in the Russian academic system.